Screening on the Presence of Plant Growth Regulators in High Biomass Forming Seaweeds from the Ionian Sea (Mediterranean Sea); Sustainability; Vol. 14, iss. 7 - Spagnuolo D. Damiano; Russo V. Valentino; Manghisi A. Antonio; Di Martino A. Antonio; Morabito M. Marina; Genovese G. Giuseppa; Trifilo P. Patrizia (2022, 2022)
Title screen